Paediatric aneurysmal bone cyst: not as easy as ABC. Issue 2 (2nd February 2018) - Unadkat, Samit; Adams, Ashok; Richards, Polly; Bajaj, Yogesh
Abstract: Aneurysmal bone cysts (ABCs) are expansile cystic lesions that can affect any bone of the body. Whilst these lesions are histologically benign, the lesions are locally aggressive and can affect the integrity of the affected bone as well as surrounding structures. ABCs arising in the head and neck region, particularly the paranasal sinuses are rare and they are limited to case reports in the literature. Due to the proximity of critical anatomical structures and the visual apparatus, the potential complications can be devastating. The present article discusses both the clinical and radiological findings of an ABC arising from the ethmoid sinuses in a 6-year-old child and the potentially challenging diagnosis with its complex ensuing surgical management. The identification of an ABC arising in the paranasal sinuses is both a diagnostic and surgical challenge and ideally requires complex management in a joint paediatric ENT and craniofacial unit.